2011
DOI: 10.1007/s00415-011-6318-0
|View full text |Cite
|
Sign up to set email alerts
|

Short-term stability of T 1 and T 2 relaxation measures in multiple sclerosis normal appearing white matter

Abstract: The presence of diffuse and widespread abnormalities within the 'normal appearing' white matter (NAWM) of multiple sclerosis (MS) brain has been established. T(1) histogram analysis has revealed increased T(1) (related to water content) in segmented NAWM, while quantitative assessment of T(2) relaxation measures has demonstrated decreased myelin water fraction (MWF, related to myelin content) and increased geometric mean T(2) (GMT(2)) of the intra/extracellular water pool. Previous studies with follow-up perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…This study is one of the largest so far to report associations between any measured hippocampal integrity and cognitive ability (Adriano et al, 2012). Where previous studies have successfully applied these techniques to pathological conditions such as brain tumour or multiple sclerosis (Davies et al, 2004; Liang et al, 2012), Alzheimer’s disease (Hanyu et al, 2005; Hong et al, 2010; Ropele et al, 2012), dementia with lewy bodies (Hanyu et al, 2005) and cerebrovascular disease (Foerster et al, 2012), we have shown their usefulness in providing more sensitive measures of brain structure than volumetric analysis in detecting subtle associations with cognitive performance. Another strength of the study is the access to early life cognitive data, age 11 IQ, allowing us to control for prior ability when looking at associations between cognitive ability in later life and brain size.…”
Section: Discussionmentioning
confidence: 96%
“…This study is one of the largest so far to report associations between any measured hippocampal integrity and cognitive ability (Adriano et al, 2012). Where previous studies have successfully applied these techniques to pathological conditions such as brain tumour or multiple sclerosis (Davies et al, 2004; Liang et al, 2012), Alzheimer’s disease (Hanyu et al, 2005; Hong et al, 2010; Ropele et al, 2012), dementia with lewy bodies (Hanyu et al, 2005) and cerebrovascular disease (Foerster et al, 2012), we have shown their usefulness in providing more sensitive measures of brain structure than volumetric analysis in detecting subtle associations with cognitive performance. Another strength of the study is the access to early life cognitive data, age 11 IQ, allowing us to control for prior ability when looking at associations between cognitive ability in later life and brain size.…”
Section: Discussionmentioning
confidence: 96%
“…Myelin water imaging was shown to have high reproducibility in healthy brains, both longitudinally and between imaging sites using the same scanner type and the same protocol [ 47 , 48 ]. Moreover, MWF in the normal appearing white matter of people with multiple sclerosis was also shown to be stable over at least six months [ 49 ]. In a guinea pig model of demyelination (experimental allergic encephalomyelitis), a decrease in the short T2 component was observed, which was consistent with histological myelin loss [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intra‐subject registration was performed with FLIRT (correlation ratio cost function, six degrees of freedom, trilinear interpolation) following the identification of the voxel location on the T I = 1500 ms IR‐ T 1 image and co‐registering all T I = 1500 ms IR‐ T 1 images and voxel maps to the 3D‐ T 1 of each volunteer (supplementary material). Following quality assurance, absolute metabolite concentrations, [met], were calculated based on voxel tissue composition, with corrections for water relaxation; for details please see the supplementary material. To avoid a bias in rejecting metabolite values from lower concentrations, individual metabolite measurements were only rejected if the absolute Cramér‐Rao lower bound error was greater than 30% of the median measured concentration …”
Section: Methodsmentioning
confidence: 99%